CHALLENGES AND OPPORTUNITIES OF WOMEN'S PEACE BUILDING ACTIVITIES IN NAIROBI COUNTY KENYA - Iteyo, Prof. Chrispinous; Mumbi, Alice (Journal of Public Policy and Administration, 2020)
Purpose: To examine the challenges and opportunities of women's peace building activities in Nairobi County Kenya. Methodology: The study used descriptive research design. The study focused on the individual women who were involved in peace building activities. Data was gathered through questionnaires, interviews, and FGDs. In total, the researcher conducted 17 FGDs, consisting of 8-12 people. A total of 386 respondents filled the semi structured questionnaire. Simple random sampling was used to select the respondents to fill the questionnaire. Purposive sampling was used to select the members to participate in the FGDs. Statistical Package for Social Sciences (SPSS) version 22 was used to analyze quantitative data. Percentages, frequencies, figures, bar charts, pie charts and tables were used to present results. Qualitative data was analyzed using coding and thematic analysis. Results were presented in form of themes and verbatim. Results: When grassroots women talk to youths, the most likely perpetrators of violence, they try to make them understand the consequences of violence. They also make them understand that destroying property only results in the suffering of the community. The study found that the impediments to women's peacebuilding effort include lack of funding, insufficient human resource, tribalism, gender stereotypes and chauvinism, and poor infrastructure. The opportunities that can be used to promote women peacebuilding activities during elections include public sensitization, security and vigilance, and the building bridges initiative. Unique contribution to theory, practice and policy: Women experience inadequacy in their community activities to uphold peace. The government should come up with proper structures to help fund women groups that normally take part in peacebuilding initiatives. Kenyan government should partner with the international bodies as well such as the UN to empower women through gender equality policies.